Correction to: Determination of the protection period of fungicides used for control of Sclerotinia stem rot in soybean through bioassay and chromatography (European Journal of Plant Pathology, (2021), 10.1007/s10658-021-02212-z) - Miorini, Thomas J. J.; Raetano, Carlos Gilberto [UNESP]; Negrisoli, Matheus M. [UNESP]; Pérez-Hernández, Oscar (Springer Nature, 2021)
This erratum is published as several typesetting errors introduced during proofing related with Tables 2,3,4,5 and has now been corrected. Original article has been updated.